Konstruksi Moderasi Islam Dalam Kegiatan Kepramukaan Di SMK Ma’arif NU Dan SMK Nurus Salaf - Kurnia Ari Setiawan (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
The phenomenon of radicalism and intolerance has spread in the world of education, including scouting or scouting activities as mandatory extracurricular activities in schools. This happens when scouts and scout leaders promote or practice intolerant attitudes or actions towards individuals or groups based on differences in religion, ethnicity, race or other backgrounds. This is a threat to the sustainability of students' nationalism. This research aims to examine the construction of Islamic moderation in scouting activities as an effort to prevent deradicalization in educational institutions. The research method used is a qualitative case study type approach with data collection techniques through observation, interviews and document analysis. The research results show that the construction of Islamic moderation in scouting activities can be a strong basis for preventing deradicalization. Through an inclusive and dialogical approach, students are empowered to understand moderate Islamic values, avoiding extreme understandings. The existence of social, humanitarian and cooperative activities in scouting forms an attitude of tolerance and mutual respect between members, reducing the potential for radicalization.